Pemodelan Sistem Informasi Perencanaan Produksi Menggunakan Business Process Modeling Notation (BPMN) - Dudi Awalludin; Eka Nurbarokah Akbar; Asep Samsul Bakhri (Systemic: Information System and Informatics Journal, 2021)
Planning is an activity where the activity is planning something that will be carried out on the next day or time. In the production process, planning is of course very influential for the smooth production and availability of goods. In general, production planning and control can be interpreted as an activity to plan and control incoming materials, processes, and exit the production system so that market demand can be fulfilled with the right amount, right delivery time and minimum production costs. This Pruduction Planning System aims to facilitate employees in carrying out production activities, where the planning can be seen through internet or mobile media